How can "tragedies of the commons" be resolved? Social dilemmas and legislation - Erling Berge (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2023)
Humanity's problem with climate change has been likened to a 'tragedy of the commons'. If the atmosphere is seen as an open access dump for gasses like CO2 or methane, Garret Hardin's conclusion from 1968: 'Freedom in a commons brings ruin to all' is obviously correct. But how do we create a regime where access to the atmosphere is controlled? The problem of cleaning up the atmosphere has also been likened to a 'public good' problem. Stopping the emissions and cleaning up the atmosphere will cost. Each nation may reason that this cost might be postponed a year or two. The immediate problems of the society have to be solved first. And - if the rest of the world manages to retard the emissions sufficiently we might not have to pay that much. In the provision of public goods there is this free rider problem. This is the background for a closer look at Norway from our earliest legislation: Did we experience collective action problems involving social dilemmas like the tragedy of the commons or the provision of public goods? If we did, did we solve the problems by developing institutions? Problems were identified in our earliest cattle farming communities and in our medieval urban settlements. The problems could be resolved through legislation.
Keywords: P48; Q30; Q54; 330; Climate; social dilemmas; Norway; legislation